EXPERIENCE OF APPLICATION OF MODERN MEANS OF EDUCATION IN PRACTICAL LESSONS ON THE PROBABILITY THEORY (Journal of Information Technologies in Education (ITE), 2017)
The article provides an overview of innovative means of teaching students in higher education on mathematical disciplines. The need to continue research aimed at the development and introduction of educational-methodical complexes was identified. It presents the author's electronic educational-methodical complex "Workshop on Probability Theory and Random Processes" for engineering students. IT contains a complex of methodological, information and training and controlling the blocks. Evaluation of the effectiveness of the use of educational and methodical complex in practical lessons on the probability theory. In the experiment, 61 students of the 2nd year of the Institute of Management of Urban Management of the Tauride National University named after V. I. Vernadsky, was studying in the direction of "Automation and computer-integrated technologies". These students formed a control and experimental group. In the course of carrying out the pedagogical experiment the students from the experimental group saw a statistically significant improvement of the level of manifestation of cognitive, motivational, activity-based and reflective of the criteria, indicating a statistically significantly higher level of training of students of the experimental group on probability theory in comparison with students in the control group.
Keywords: complex; teaching; the probability theory; means; practice; evaluation; impact; efficiency